‘An Indigenous Fucking Blood Revival’: Pagan Aesthetics in The US Indigenous Black Metal Scene - Rivero-Vadillo, Alejandro (Complutense Journal of English Studies, 2024)
This article analyzes two different modulations of Indigenous Black Metal in the contemporary US context, specifically focusing on how Indigenous Black Metal appropriates (but also distances itself from) European conceptualizations of this Metal subgenre. In this process, it adapts its lyrics to decolonial discourses. The text argues that Pagan Black Metal, although a musical product inherently connected to European understandings of pre-Christian spirituality, has found an autochthonous way in the American scenario through a sense an Indigenous-minded aesthetic vision of European paganism. After introducing the way in which senses of local land, ancestry and paganism are intertwined in the configuration of Pagan Black Metal lyrics, the article addresses two paradigmatic examples of the American Indian approach, Nechochwen and Pan-Amerikan Native Front. These two bands replicate the aggressive sounds and ontological logics of their European counterparts, erasing, nonetheless certain thematic aspects to adapt themselves to Pan-Indigenous dialectics.